Ion channels and their inhibitors - Gupta, Satya Prakash (Springer Berlin Heidelberg, 2011)
Being the crucial components of living cells, ion channels are important targets of therapeutic agents. Historically, it has been challenging to develop drugs on this target class. A major issue with target based ion channel drug development is the identification of effective small chemical leads for medicinal chemistry optimization to the clinical candidate status. Thus enough attention has been paid to the study of structure and functions of ion channels and their potential inhibitors. The present book compiles important chapters authored by eminent workers in the field to cover important recent advances in the studies of the structure and functions of ion channels and their inhibitors, such as sodium ion, potassium ion, chloride ion, calcium ion channel inhibitors. The book may be of great use to the students and scientists working in the area of molecular biology, biochemistry, physiology, neurobiology, and medicinal chemistry.